Effectiveness of acceptance and commitment therapy on emotion regulation in epileptic patients - Hamideh Sadeghnezhad; Saeed Teimory; Mehdi Amiri (Shahid Beheshti University of Medical Sciences, 2021)
Background: Epilepsy can severely affect cognitive-emotional and behavioral function. Using an appropriate treatment method to deal with it in order to treat emotional disorders can be an effective action due to the importance of this disorder. This study attempted to investigate the effectiveness of Acceptance and commitment therapy (ACT) on the emotion regulation in patients with epilepsy. Methods: It was a quasi-experimental study (pretest-posttest design with equal control group) and the sample consisted of 30 patients with epilepsy selected purposefully and assigned into experimental (n=15) and control (n=15) groups randomly. The instrument included the Garnefski et al. Cognitive Emotion Regulation Questionnaire (CERQ). Data were analyzed using SPSS software version 21 conducting MANCOVA and ANCOVA analysis of covariance. Results: The results showed that the ACT decreased negative emotion regulation and also increased positive emotion regulation in patients with epilepsy in the experimental group compared to the control group. The results of one-way analysis of covariance with the pretest control showed that there was a significant difference between the experimental and control groups in patients with epilepsy in terms of positive emotion regulation (F = 100.55, p <0.001) and negative emotion regulation (F = 154.64, p <0.001). Conclusion: It can be argued that ACT reduced negative emotion regulation and increased positive emotion regulation in patients with epilepsy.